Steam Reforming of Glycerol over Nickel-based Catalyst - Sabri, Muhammad Amirul Faris (Universiti Teknologi PETRONAS, 2016)
Hydrogen demand has been increased nowadays in order to satisfy the needs of the industry. However, the current raw material in production of hydrogen which is methane has been reduced eventually due the decrement of the natural resources. It is expected to run off within half century from now. Hydrogen has been used widely in industry such that it contributes in the production of ammonia, transportation as a clean gas and housing area. In order to produce hydrogen, the researcher has used the glycerol for steam reforming process. For this project, the researcher has to prepare four sample of Nickel-Calcium Alumina catalyst that consists of different composition of the calcium with different composition by using wet impregnation of sonochemical methods. The catalysts then have been characterized by using many techniques involving X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM).